Answer:
21/8
Explanation:
Simplify the following:
6 + 1/4 - (3 + 5/8)
Put 3 + 5/8 over the common denominator 8. 3 + 5/8 = (8×3)/8 + 5/8:
6 + 1/4 - (8×3)/8 + 5/8
8×3 = 24:
6 + 1/4 - (24/8 + 5/8)
24/8 + 5/8 = (24 + 5)/8:
6 + 1/4 - (24 + 5)/8
24 + 5 = 29:
6 + 1/4 - 29/8
Put 6 + 1/4 - 29/8 over the common denominator 8. 6 + 1/4 - 29/8 = (8×6)/8 + 2/8 - 29/8:
(8×6)/8 + 2/8 - 29/8
8×6 = 48:
48/8 + 2/8 - 29/8
48/8 + 2/8 - 29/8 = (48 + 2 - 29)/8:
(48 + 2 - 29)/8
| 1 |
| 4 | 8
+ | | 2
| 5 | 0:
(50 - 29)/8
| 4 | 10
| 5 | 0
- | 2 | 9
| 2 | 1:
Answer: 21/8